MENINGKATKAN HASIL BELAJAR SISWA TENTANG KONSEP JARINGAN TUMBUHAN MELALUI MODEL PEMANCAR PADA SISWA KELAS XI IPA 3 SMAN 1 SAMPARA - Ferdinan Lekman (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2021)
This research is a Classroom Action Research in an effort to improve studentlearning outcomes about the concept of plant tissue through the use of amicroscope, android, note book and chart (transmitter) which is an acronym forthe sentence use of a microscope, android, note book and chart. The aims of thisresearcher are to: (1) Improve student learning outcomes about plant tissueconcepts through the use of microscopes, androids, note books and charts in classXI IPA 3 SMA Negeri 1 Sampara odd semester 2017-2018 school year, (2 )Increase student learning activities about the concept of plant tissue through theuse of microscopes, androids, note books and charts in class XI IPA 3 SMANegeri 1 Sampara in odd semesters in the 2017-2018 learning year, (3) Increaseteacher teaching activities about network concepts through the use of amicroscope , android, note books and charts in class XI IPA 3 SMA Negeri 1Sampara odd semester 2017-2018 learning year. The formulation of the problemin this study is "Can the use of microscopes, androids, note books and chartsimprove student learning outcomes on the concept of Networking? plants in classXI IPA 3 SMA Negeri 1 Sampara in the academic year 2017-018. The hypothesisof this classroom action research is that the use of a microscope, android, notebook and chart (transmitter) will improve student learning outcomes about theconcept of plant tissue in science class 3 SMA Negeri 1 Sampara students in the2017-2018 school year. Based on the results of analysis and reflection, it can beconcluded that: Student activity during learning activities increased. In the firstcycle, the average student activity was 77.78%. While in the second cycle ofstudent activities reached an average of 97%. This means that there is anincrease from cycle I to cycle II of 19.22 ( 24,71 % ) . Thus, student learningactivities have increased from cycle I to cycle II by 16.43%. Teacher teachingactivities increased in the first cycle. The average process score for teacheractivity activities in the first cycle was 72.5%. While in the second cycle theaverage teacher teaching activity was 97.5%. The increase in teacher activityfrom cycle I to cycle II is 25%. Meanwhile, student learning outcomes haveincreased, namely the average in the first cycle was 77.37 and in the second cyclereached 92.46. This means that there is an increase of 15.07 or 19.8%. Thus, itcan be concluded that student learning outcomes increase about the concept ofplant tissue through the TRANSMITTER Model in class XI IPA 3 students of SMANegeri 1 Sampara in the 2017-2018 school year.